Gene within gene configuration and expression of the Drosophila melanogaster genes lethal(2) neighbour of tid [l(2)not] and lethal(2) relative of tid[l(2)rot]. - Kurzik-Dumke, U.; Kaymer, M.; Gundacker, D.; Debes, A.; Labitzke, K. (Gene, 1997)
In this paper, we describe the structure and temporal expression pattern of the Drosophila melanogaster genes l(2)not and l(2)rot located at locus 59F5 vis à vis the tumor suppressor gene l(2)tid described previously and exhibiting a gene within gene configuration. The l(2)not protein coding region, 1530 nt, is divided into two exons by an intron, 2645 nt, harboring the genes l(2)rot, co-transcribed from the same DNA strand, and l(2)tid, co-transcribed from the opposite DNA strand, located vis à vis. To determine proteins encoded by the genes described in this study polyclonal rabbit antibodies (Ab), anti-Not and anti-Rot, were generated. Immunostaining of developmental Western blots with the anti-Not Ab resulted in the identification of a 45-kDa protein, Not45, which is smaller than the Not56 protein predicted from the sequence. Its localization in endoplasmic reticulum (ER) was established by immunoelectron microscopy of Drosophila melanogaster Schneider 2 cells. Not45 shows significant homology to yeast ALG3 protein acting as a dolichol mannosyltransferase in the asparagine-linked glycosylation. It is synthesized ubiquitously throughout embryonic life. The protein predicted from the l(2)rot sequence, Rot57, shows a homology to the NS2B protein of the yellow fever virus1 (yefv1). The results of l(2)rot RNA analysis by developmental Northern blot and by in situ RNA localization, as well as the results of the protein analysis via Western blot and immunohistochemistry suggest that l(2)rot is transcribed but not translated. Since RNAs encoded by the genes l(2)tid and l(2)rot are complementary and l(2)rot is presumably not translated we performed preliminary experiments on the function of the l(2)rot RNA as a natural antisense RNA (asRNA) regulator of l(2)tid expression, expressed in the same temporal and spatial manner as the l(2)tid- and l(2)not RNA. l(2)tid knock-out by antisense RNA yielded late embryonic lethality resulting from multiple morphogenetic defects.